2020
DOI: 10.1186/s12887-020-2012-7
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Interventions to Manage Self-Regulation in Type 1 Diabetes (AIMS-T1D): randomized control trial study protocol

Abstract: Background: Self-regulation (SR), or the capacity to control one's thoughts, emotions, and behaviors in order to achieve a desired goal, shapes health outcomes through many pathways, including supporting adherence to medical treatment regimens. Type 1 Diabetes (T1D) is one specific condition that requires SR to ensure adherence to daily treatment regimens that can be arduous and effortful (e.g., monitoring blood glucose). Adolescents, in particular, have poor adherence to T1D treatment regimens, yet it is esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…Measured in the present study in terms of temperamental effortful control, self-regulation showed associations with usage activity and perceived usefulness of the intervention. This finding supports previous results on self-regulation's role in achieving health-related outcomes ( Berg et al, 2014 ; Miller et al, 2020 ), and implies that the Youth Compass program could potentially be more beneficial to adolescents with higher self-regulation skills because they are more likely to engage with the program material and its objectives. Higher perceived usefulness of the Youth Compass program could possibly be due to higher adherence facilitated by self-regulatory mechanisms.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Measured in the present study in terms of temperamental effortful control, self-regulation showed associations with usage activity and perceived usefulness of the intervention. This finding supports previous results on self-regulation's role in achieving health-related outcomes ( Berg et al, 2014 ; Miller et al, 2020 ), and implies that the Youth Compass program could potentially be more beneficial to adolescents with higher self-regulation skills because they are more likely to engage with the program material and its objectives. Higher perceived usefulness of the Youth Compass program could possibly be due to higher adherence facilitated by self-regulatory mechanisms.…”
Section: Discussionsupporting
confidence: 90%
“…Adherence to treatment by adolescents has been found to be connected to factors such as self-regulation skills ( Berg et al, 2014 ; Graziano et al, 2011 ; Miller et al, 2020 ) and the perceived threat of physical disease affecting mental well-being ( Kyngäs, 2007 ). Demographic variables such as age, gender, and parents' educational level have received mixed results, with some studies finding connections to adherence and some not (see, e.g., Calear et al, 2013 , Christensen et al, 2009 , Garrido et al, 2019 , Kristensen et al, 2018 , Marko-Holguin et al, 2010 , Mattila et al, 2016 , Neil et al, 2009 , Williams et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Study 2, which began data collection in April 2019, was an observational study of parents of youth with T1D. For both studies, participants were recruited from pediatric endocrinology clinics at the University of Michigan and via online methods ( Miller et al, 2020 ). Study 1 eligibility criteria were: youth (a) 13–17 years old; (b) diagnosed with T1D for at least 6 months; (c) had HbA1c ≥ 7.0%; (d) resided with participating parent/legal guardian at least 50% of the time; (e) had regular access to a smartphone and Wi-Fi; (f) no psychiatric or cognitive conditions that would impede ability to participate; and (g) was sufficiently fluent in English to complete study activities.…”
Section: Methodsmentioning
confidence: 99%
“…Another aspect of reproductive health for which tools and findings from SOBC projects may prove useful is the developmental considerations for self-regulation investigated in a study of diabetes self-management in adolescents [ 38 ]. Self-regulation includes the capacity to control one’s thoughts, emotions, and behavior to achieve a goal, which overlaps somewhat with self-efficacy, but the emotion regulation component is unique.…”
Section: Promising New Directionsmentioning
confidence: 99%
“…SOBC-funded projects have used an experimental medicine approach to investigate a variety of mechanistic targets and health behaviors across the domains of self-regulation, interpersonal and social processes, and stress resilience and stress reactivity, with links to health outcomes relevant to multiple NIH Institutes and Centers. These health outcomes include, for example, cardiovascular health [ 7 , 8 ], sleep health [ 9 ], stress and physical activity [ 10 ], opioid use disorder [ 11 ], obesity [ 12–14 ], prediabetes and diabetes management [ 15 , 16 ], smoking cessation [ 17 ], and breast cancer survivorship among African American women [ 18 ]. Two areas of research not addressed by current SOBC-funded projects provide promising opportunities to apply a mechanisms-focused approach to behavior change research: reproductive health and COVID-19 vaccine uptake.…”
Section: Introductionmentioning
confidence: 99%